REGARDING DISPUTE AND ARBITRATION - Darwis, Hanafi (Universitas Ekasakti, 2019)
It shall be necessarily acknowledged that a dispute is usually originated from such a situation in which a party feels harmed by the other party. Unsatisfied expression shall come out if there is any conflict of interest. In respect of which, people shall have such a certain way to settle a conflict or dispute itself, in which the process of dispute settlement engaged herein may be taken through both formal and informal approaches. In relation to which, Arbitration Agency may receive a request raised by the parties in such an agreement and give a binding opinion regarding the matters pertaining to the aforementioned agreement, for instance, if there is any interpretation of any unclear provision; there is any addition or variation in the provision with respect to the existence of any new circumstance. Accordingly, the issuance of opinion by arbitration agency shall cause the both parties bound to it, if a party’s action is in violation to the aforesaid opinion, it shall be deemed to breach the agreement, and against the aforesaid binding opinion, any legal remedy or protest whatsoever may not be filed either in the form of legal proceeding of Appeal or Cassation.